Reducing hops without extra power: Impact of deployment height on low-power multihop wireless network. (September 2017) - Jeong, Hoon; Lee, Changwon; Ryu, Jaehong; Choi, Byung-Chul; Ko, JeongGil; Paek, Jeongyeup
Many low-power wireless network system deployments are planned on a two-dimensional plane, while in reality, we live in a three-dimensional space. Therefore, although it is essential to well consider the impact of height on the overall wireless system performance, this aspect has often been overlooked if not neglected with simplifying assumptions. Our work takes an empirical effort in quantifying the impact of height on a low-power wireless system's performance. Specifically, we use CC2420 radio–based wireless sensor network motes to quantify the impact of device deployment height on the connectivity and energy efficiency of low-power wireless networks. In addition, to validate the newly proposed sub-GHz low-power radios, we also experiment on the performance of CC1200 narrowband low-power radios to show that increasing a small amount of height in the node deployment phase can lead to drastic improvements in radio coverage and packet delivery performance. Such an observation can naturally lead to the reduction of network depth in a multihop wireless network for a given target deployment field; thus, it can potentially improve the energy efficiency of the overall system by suppressing the number of packet relay transmissions. We support our findings and observations through experiments on real embedded devices.